2007
DOI: 10.1530/rep-07-0338
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic alteration of the donor cells does not recapitulate the reprogramming of DNA methylation in cloned embryos

Abstract: Epigenetic reprogramming is a prerequisite process during mammalian development that is aberrant in cloned embryos. However, mechanisms that evolve abnormal epigenetic reprogramming during preimplantation development are unclear. To trace the molecular event of an epigenetic mark such as DNA methylation, bovine fibroblasts were epigenetically altered by treatment with trichostatin A (TSA) and then individually transferred into enucleated bovine oocytes. In the TSA-treated cells, expression levels of histone de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 32 publications
(34 reference statements)
4
52
0
Order By: Relevance
“…Thus, several investigators proposed that failure of DNA demethylation causes incomplete nuclear reprogramming in cloned embryos [16,18,43]. Wee et al [27] reported that the DNA methylation level in the bovine satellite I sequence of TSA-treated cells was significantly lower than that of untreated cells and that such DNA methylation levels remained in blastocyst embryos after SCNT. In the present study, we demonstrated that DNA methylation of this sequence was maintained at a high level in SCNT embryos treated with 50 nM TSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, several investigators proposed that failure of DNA demethylation causes incomplete nuclear reprogramming in cloned embryos [16,18,43]. Wee et al [27] reported that the DNA methylation level in the bovine satellite I sequence of TSA-treated cells was significantly lower than that of untreated cells and that such DNA methylation levels remained in blastocyst embryos after SCNT. In the present study, we demonstrated that DNA methylation of this sequence was maintained at a high level in SCNT embryos treated with 50 nM TSA.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that treatment with trichostatin A (TSA), which is a histone deacetylase inhibitor, improves in vitro blastocyst development, embryonic stem cell derivation and full-term development of mouse SCNT embryos. Furthermore, TSA treatment also improves preimplantation development of porcine [23,24] and bovine [25][26][27] SCNT embryos. In bovine embryos, TSA treatment after SCNT inhibited histone deacetylation and increased the levels of histone acetylation compared with untreated SCNT embryos [25,26].…”
mentioning
confidence: 95%
“…In serial cloning, accumulation of epigenetic modifications was initially thought to make it impossible to clone past several repetitions [110,111]. However, with recent advances in SCNT, it may be possible to repair epigenetic modifications by chemical treatment [112][113][114][115][116][117][118]. Thus, somatic cell cloning may be repeated beyond previously expected limits (Wakayama, personal communication).…”
Section: Development Of Genetically Modified Pigs For Xenotransplantamentioning
confidence: 99%
“…However, this process needed for a differentiated donor nucleus to achieve embryonic status is delayed and incomplete in NT embryos [5]. In fact, many studies have demonstrated that epigenetic statuses such as DNA methylation and histone acetylation, are abnormally established in NT embryos during preimplantation development [6][7][8][9][10][11][12]. As a result, abnormal gene expression including imprinted genes [10,[13][14][15] can prevent normal development of NT embryos [16].…”
mentioning
confidence: 99%
“…Therefore, the level of DNA methylation in normal embryos during preimplantation development is relatively low [22,23]. However, previous studies have shown that the level of DNA methylation in NT embryos is higher than in normal embryos and is more similar to somatic cells, since a somatic genome that is injected into an oocyte does not undergo demethylation [6][7][8][9]11]. This hypermethylation phenomenon is frequently associated with the genome of NT embryos and is considered one of the reasons for abnormal gene expression and low cloning efficiency [21].…”
mentioning
confidence: 99%